Effect of nickel (ll) sorption on the growth and morphology of anabaena laxa and nostoc commune. - Santos, Catherine M. 4 0 16; 5 (2005)
u
Thesis:(B.S. Biology) Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2